PENDEKATAN ESTETIKA PADA DESAIN PESAN MULTIMEDIA PEMBELAJARAN - Moeljadi Pranata (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
The development of multimedia design is influenced by various theories such as visual aesthetic principles. Aesthetic principles are used to guide the design process as well as play a role to increase the attractiveness of the message. However, along with the progress  in  computer  graphics,  graphic  design  aesthetic  applications in  multimedia learning  has  led  to  the  concept  of  multimedia  performances entertaining, aesthetic oriented. Additionally, this technology, along with multimedia technology, has expanded the field of professional designing multimedia learning beyond learning profession such as graphic designer profession.